Development of E-Learning Materials Assisted by Augmented Reality on Human Digestive System Material to Improve Elementary School Students' Learning Outcomes - Muhammad Wahyu Agung Risqiyono; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop, test the feasibility, effectiveness, and practicality of Augmented Reality (AR)-assisted e-learning materials to improve student learning outcomes. This study is a Development Research (R&D) using the Borg and Gall model. This study involved 42 fifth grade students of Kedungmundu State Elementary School (SDN) in the 2024/2025 academic year, with a small-scale trial on 15 VA class students and a large-scale trial on 27 VB class students. Data collection techniques used test techniques (pretest - posttest) and non-test in the form of interview results, questionnaires, observations, score lists, and documentation. The results of validation by material, language, and media experts which showed that AR-assisted e-learning materials were declared "very feasible" with an average score of 89%. The practicality of e-teaching materials is shown from the results of the questionnaire responses of teachers and students to the use of e-teaching materials assisted by AR showing a "very positive" level of satisfaction, with a score of 97% from teachers and 86% from students. The effectiveness of e-teaching materials assisted by AR is proven through the results of the t-test with a significance value of 0.000 (<0.05) and an N-gain of 0.67, which is included in the "moderate" category. The results of the study indicate that e-teaching materials assisted by AR meet the criteria of being feasible, practical, and effective in improving learning outcomes in class V science learning at SDN Kedungmundu.